Performance Evaluation of the Monocrystalline Solar Module Within a Wide Range of Solar Radiation and Operating Solar Module Temperature (Journal of Engineering, 2026)
In this work, an experimental (hardware-in-the-loop) and numerical study of a 50W photovoltaic (PV) module with an ML2440 solar charge controller is presented under different levels of solar irradiance conditions, using a resistive load. Three test cases were considered: no tracking and two resistive loads (90 Ω and 115 Ω). Theoretical power and efficiency were predicted from the incident solar irradiance, panel temperature and module characteristics, and experimental measurements were then juxtaposed with the calculated values to assess both the model’s accuracy and the controller’s performance. The maximum measured output reached 49.70 W when the irradiance was 1000 W/m², and the load resistance was set to its optimum of 115 Ω, which nearly matches the predicted 50.30 W; this corresponds to a relative discrepancy of roughly 1.2 %. By contrast, the highest power recorded without tracking was 46.51 W, and the average departures from the ideal power were larger. An examination of the RMSE revealed that the scenario without tracking incurred the greatest deviations—7.92 W in power and a 2.84 % drop in efficiency—whereas the 115 Ω and 90 Ω loads each produced smaller RMSE values than the other load conditions, reflecting a reduction of the error to as low as 4.12 W and 1.87 %.The results of the relative error analysis also verified the outstanding characteristics of MPPT-based configurations. The results achieved confirm the effectiveness of the ML2440 controller for improving PV output by optimal load matching and demonstrate that the proposed numerical model can be utilized as a predictive tool to evaluate the performance of PV systems.